Dual-Specificity Phosphatase 12 Targets p38 MAP Kinase to Regulate Macrophage Response to Intracellular Bacterial Infection - Cho, Sharol Su Lei; Han, Jian; James, Sharmy J.; Png, Chin Wen; Weerasooriya, Madhushanee; Alonso, Sylvie; Zhang, Yongliang (Frontiers in Immunology, 2017)
The mitogen-activated protein kinase (MAPK) cascades are activated in innate immune cells such as macrophages upon the detection of microbial infection, critically regulating the expression of proinflammatory cytokines and chemokines such as TNF-α, IL-6, and MCP-1. As a result, activation of MAPKs is tightly regulated to ensure appropriate and adequate immune responses. Dual-specificity phosphatases (DUSPs) are a family of proteins which specifically dephosphorylates threonine and tyrosine residues essential for MAPK activation to negatively regulate their activation. DUSP12 is a member of atypical DUSPs that lack MAPK-binding domain. Its substrate and function in immune cells are unknown. In this study, we demonstrated that DUSP12 is able to interact with all the three groups of MAPKs, including extracellular signal-regulated protein kinase, JNK, and p38. To investigate the function of DUSP12 in macrophages in response to TLR activation and microbial infection, we established RAW264.7 cell lines stably overexpressing DUSP12 and found that overexpression of DUSP12 inhibited proinflammatory cytokine and chemokine production in response to TLR4 activation, heat-inactivated Mycobacterium tuberculosis stimulation as well as infections by intracellular bacteria including Listeria moncytogenesis and Mycobacterium bovis BCG by specifically inhibiting p38 and JNK. In addition, a scaffold protein known as signal transducing adaptor protein 2 (STAP2), was found to mediate the interaction between DUSP12 and p38. Thus, DUSP12 is a bona fide MAPK phosphatase, playing an important role in MAPK-regulated responses to bacterial infection. Our study provides a model where atypical DUSPs regulate MAPKs via scaffold, thereby regulating immune responses to microbial infection.